KONSEP PENDIDIKAN AKHLAK MENURUT IBNU MISKAWAIH - Miswar Rasyid (Tazkiya: Jurnal Pendidikan Islam, 2020)
Ibn Miskawaih had advantages in the field of moral philosophy, because since his youth, he had studied Persian and Greek morals. According to Ibn Miskawaih, morality is a state of the soul that invites a person to do actions without thinking and calculated beforehand. So that it can be used as human nature and the results of the exercises that have been done, to become the nature of self that can give birth to good khuluq. Miskawaih is not only a philosopher but he is a moralist, literary, chemist, historian. So the work he produces is not only about one scientific aspect. According to Ibn Miskawayh, the goal of moral education is the realization of an inner attitude that is capable of spontaneously encouraging all the good deeds to be born so as to achieve perfection and obtain true and perfect happiness. The aim of moral education formulated by Ibn Miskawaih is the realization of inner attitude which is able to encourage spontaneously to give birth to all good-value deeds. So as to achieve perfection and obtain perfect and complete true happiness, including the happiness of human life in the broadest sense. Keyword: Education, Morals And Ibn Miskawaih.